The Current State-of-the-Art of the Processes Involved in the Chemical Recycling of Textile Waste - Urbain Nshokano Ndagano; Laura Cahill; Ciara Smullen; Jennifer Gaughran; Susan M. Kelleher (Molecules)
The textile industry’s rapid growth and reliance on synthetic fibres have generated significant environmental pollution, highlighting the urgent need for sustainable waste management practices. Chemical recycling offers a promising pathway to reduce textile waste by converting used fibres into valuable raw materials, yet technical challenges remain due to the complex compositions of textile waste, such as dyes, additives, and blended fabrics.